Physical properties of 20% Cr-doped Pr0.7Ca0.3MnO3 perovskite. Issue 9 (November 2015) - Selmi, A.; Bettaibi, A.; Rahmouni, H.; M'nassri, R.; Chniba Boudjada, N.; Chiekhrouhou, A.; Khirouni, K.
Abstract: A systematic study on the structural, magnetic, magnetocaloric and electrical properties of Pr0.7 Ca0.3 Mn1− x Cr x O3 ( x =0 and x =0.2) manganites is carried out. The substitution of Mn by Cr destroyed the charge order state observed in the parent compound and induced a ferromagnetic phase at low temperatures. The chromium substituted sample exhibits a maximum value of magnetic entropy change |∆ S max |=2.87 J kg −1 K −1 and a large relative cooling power with a maximum value of 253.2 J/kg under an applied field of 5 T, respectively. When chromium is added, the electrical resistance increases significantly at a specific temperature. It is found that the activation energy increases from E a =26 meV for the parent compound to E a =150 meV for the 20% Cr-doped material due to the localization of the active electron. Electronic conduction mechanism is found to be dominated by polaron hopping process. The presence of electrical relaxation phenomenon in the material and the contribution of grain boundaries in conduction process are confirmed by the complex impedance analysis.